Cell adhesion in Drosophila: versatility of cadherin and integrin complexes during development. - Bulgakova, N.A.; Klapholz, B.; Brown, N.H. (Current Opinion in Cell Biology, 2012)
We highlight recent progress in understanding cadherin and integrin function in the model organism Drosophila. New functions for these adhesion receptors continue to be discovered in this system, emphasising the importance of cell adhesion within the developing organism and showing that the requirement for cell adhesion changes between cell types. New ways to control adhesion have been discovered, including controlling the expression and recruitment of adhesion components, their posttranslational modification, recycling and turnover. Importantly, even ubiquitous adhesion components can function differently in distinct cellular contexts.